Can reverse shoulder arthroplasty in post-traumatic revision surgery restore the ability to perform activities of daily living? - Maier, Michael Wolfgang; Zeifang, Felix; Caspers, Mira Sabina; Dreher, Thomas; Klotz, Matthias C. M.; Rettig, Oliver; Wolf, Sebastian Immanuel (Orthopaedics & traumatology, 2015)
Failed shoulder arthroplasty and failed internal fixation in fractures of the proximal humerus can benefit from implantation of a reverse total shoulder arthroplasty (RSA). While there is some evidence that RSA can improve function regarding range of motion (ROM), pain, satisfaction, and strength, there is sparse data how this translates into activities of daily living (ADLs). A marker-based 3D video motion analysis system has recently been designed that can measure changes of ROM in dynamic movements in every plane. The hypothesis was that a gain of maximum ROM also translates into the ability to perform ADLs and into a significant increase of ROM in ADLs. Six consecutive patients (5 women, 1 man; 2× failed arthroplasty, 4× failed open reduction and internal fixation) who received RSA were examined the day before and 1 year after shoulder replacement. A 3D motion analysis system using a novel upper extremity model measured active maximum values and ROM in four ADLs. Comparing the pre- to the 1-year postoperative status, RSA resulted in a significant increase in mean maximum values for active flexion (humerus to thorax) of 37° (S.D. ±23°), from 50 to 87° [P=0.005], and for active abduction averaging of 17° (S.D. ±13°), from 52 to 69° [P=0.027]. The extension decreased significantly by about 8° (S.D. ±16°), from a mean of 39 to 31° [P=0.009]. For active adduction and internal and external rotation, there were trends for improvements, but no significant changes. Only three additional tasks of the ADL (out of 13/24 preoperatively) could be performed after revision surgery. Comparing the preoperative to the postoperative ROM in the ADLs in flexion/extension, ROM improved significantly in one (“tying an apron”) of four ADLs. There were no significant changes in the abduction/adduction and internal/external rotation in any ADLs. RSA in revision cases significantly improved maximum active flexion and abduction, but decreased extension in this series. However, the patients were only able to use this greater ROM to their benefit in one of four ADLs.
Gesehen am 27.07.2017